The Evaluation of the Democratic Consolidation in the Republic of Czech as the Effect of Democratization Process Durability - Kubas, Sebastian (Political Preferences, 2017)
The process of democratization leads to implementation of democratic values among society and institutional pattern in political system. It is a complicated and multi-staged road. Each stage and dimension has its own qualities. The article presents both theoretical conception of the process of democratization and empirical example of the Republic of Czech. There are some general and specific Czech qualities of all stages of the process of democratization: erosion of undemocratic regime, transition and democratic consolidation. The last one is evaluated in the article in the lime of quantitative and qualitative analysis. Key words: process of democratization, democratic consolidation, Czech Republic